Mechanisms Involved in Microglial-Interceded Alzheimer’s Disease and Nanocarrier-Based Treatment Approaches - Shadab Md (MDPI AG, 2021)
Alzheimer’s disease (AD) is a common neurodegenerative disorder accountable for dementia and cognitive dysfunction. The etiology of AD is complex and multifactorial in origin. The formation and deposition of amyloid-beta (Aβ), hyperphosphorylated tau protein, neuroinflammation, persistent oxidative stress, and alteration in signaling pathways have been extensively explored among the various etiological hallmarks. However, more recently, the immunogenic regulation of AD has been identified, and macroglial activation is considered a limiting factor in its etiological cascade. Macroglial activation causes neuroinflammation via modulation of the NLRP3/NF-kB/p38 MAPKs pathway and is also involved in tau pathology via modulation of the GSK-3β/p38 MAPK pathways. Additionally, microglial activation contributes to the discrete release of neurotransmitters and an altered neuronal synaptic plasticity. Therefore, activated microglial cells appear to be an emerging target for managing and treating AD. This review article discussed the pathology of microglial activation in AD and the role of various nanocarrier-based anti-Alzeihmenr’s therapeutic approaches that can either reverse or inhibit this activation. Thus, as a targeted drug delivery system, nanocarrier approaches could emerge as a novel means to overcome existing AD therapy limitations.